2019
DOI: 10.1097/md.0000000000016061
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of syndesmotic fixations in a pediatric center

Abstract: Syndesmosis injuries need to be accurately diagnosed and managed to avoid chronic pain, early arthritis, and instability. To this end, the present study aimed to analyze the epidemiology of syndesmotic injuries in a pediatric ankle fracture cohort and identify patient and surgery-related characteristics. A retrospective review of all the ankle fractures during a 12-year period at a single pediatric referral center was conducted. Inclusion criteria were: a fractured ankle that underwent a surgical fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Our finding that operative ankle fractures with and without SF had equivalent functional outcomes differs from some studies in the adult population. 19 , 26 - 29 Egol et al 27 conducted a large study on 347 patients with unstable ankle fractures, finding that those with SF had significantly worse functional outcome and pain scores at minimum one-year follow-up. Still and Atwood 29 also found that fractures requiring SF had worse functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our finding that operative ankle fractures with and without SF had equivalent functional outcomes differs from some studies in the adult population. 19 , 26 - 29 Egol et al 27 conducted a large study on 347 patients with unstable ankle fractures, finding that those with SF had significantly worse functional outcome and pain scores at minimum one-year follow-up. Still and Atwood 29 also found that fractures requiring SF had worse functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…While the effect of syndesmotic injury on functional outcome in the adult population remains unclear, data on adolescent syndesmotic injuries is even more limited. Lamer et al 19 reviewed 128 paediatric ankle fractures but only identified 11 patients that underwent SF and found similar functional outcomes at approximately one-year follow-up. Our study had a much higher proportion of skeletally mature adolescents that required SF and, therefore, we were able to perform an adequately powered comparison between adolescent ankle fractures treated with and without SF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations